The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fneur.2021.619721
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Biomarkers: Are We There Yet?

Abstract: Background: Distinguishing between stroke subtypes and knowing the time of stroke onset are critical in clinical practice. Thrombolysis and thrombectomy are very effective treatments in selected patients with acute ischemic stroke. Neuroimaging helps decide who should be treated and how they should be treated but is expensive, not always available and can have contraindications. These limitations contribute to the under use of these reperfusion therapies.Aim: An alternative approach in acute stroke diagnosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 132 publications
(37 reference statements)
0
87
0
4
Order By: Relevance
“…In many areas of medicine, biomarkers are currently used to help to diagnose, establish prognoses, and to prescribe therapeutics to specific groups of patients that benefit the most from differentiated treatments due to having particular phenotypes [ 1 ]. Moreover, in neurology, several studies that evaluated biomarkers have been conducted in recent years, namely in the area of stroke [ 2 ]. When compared to other medical areas, the application of biomarkers to the field of cerebrovascular pathology has some obstacles: (a) the presence of the blood–brain barrier that poses difficulties and delays the release of proteins of neuronal or glial origin into the bloodstream after stroke; and (b) many of the potential serum biomarkers of cerebral ischemia and inflammation have low specificity and may also be increased in situations that can be confounded with stroke as they may present in a similar way such as acute myocardial infarction or central nervous system inflammation [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…In many areas of medicine, biomarkers are currently used to help to diagnose, establish prognoses, and to prescribe therapeutics to specific groups of patients that benefit the most from differentiated treatments due to having particular phenotypes [ 1 ]. Moreover, in neurology, several studies that evaluated biomarkers have been conducted in recent years, namely in the area of stroke [ 2 ]. When compared to other medical areas, the application of biomarkers to the field of cerebrovascular pathology has some obstacles: (a) the presence of the blood–brain barrier that poses difficulties and delays the release of proteins of neuronal or glial origin into the bloodstream after stroke; and (b) many of the potential serum biomarkers of cerebral ischemia and inflammation have low specificity and may also be increased in situations that can be confounded with stroke as they may present in a similar way such as acute myocardial infarction or central nervous system inflammation [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive diagnostic efficacy of blood biomarkers has been seriously underestimated or even ignored in stroke. However, with the recent research development, their application value has been revisited ( El-Serag et al, 2014 ; Valappil et al, 2017 ; Lee et al, 2018 ; Dagonnier et al, 2021 ). Unlike univariate analysis in neuroimaging, some preliminary studies related to stroke classification have focused on models that combine blood biomarkers, showing great potential ( Misra et al, 2017 ; Makris et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma molecular biomarkers, including proteins, metabolites, lipids, and nucleic acids, can be used alone or in combination (panels, scores, or indices), are the potential ideal candidates [ 30 ] to detect acute stroke, differentiate IS from HS and stroke mimics, extrapolate the infarct volume, identify the stroke cause, and predict the short/long-term outcome [ 31 ]. This would allow a substantial time gain in prehospital settings and, eventually, avoid futile transfers to comprehensive stroke centers (CSCs) [ 32 , 33 ]. Over the past years, several studies identified more than 150 putative molecular biomarkers in patients’ serum for early diagnosis and prognosis [ 16 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…This would allow a substantial time gain in prehospital settings and, eventually, avoid futile transfers to comprehensive stroke centers (CSCs) [ 32 , 33 ]. Over the past years, several studies identified more than 150 putative molecular biomarkers in patients’ serum for early diagnosis and prognosis [ 16 , 33 , 34 , 35 , 36 ]. Despite several of these having shown great potential, there is currently no blood biomarker for clinical stroke diagnosis.…”
Section: Introductionmentioning
confidence: 99%